Risiko und HIV / Aids in Botswana: Leben in der Pandemie - Bochow, Astrid (Dietrich Reimer Verlag, 2020)
Botswana, one of the few middle-income countries in Africa, has one of the highest HIV rates in the world. In her book Astrid Bochow deals with the Botswana middle class, which has formed since the 1980s: How do these privileged groups handle the permanent threat of infection and the experience of illness and loss? How does their everyday life in family and partnership look like? And what new social and economic opportunities open up for them in the crisis? The author analyzes the resulting political, medical and social discourses on family and health.